Kinerja Ombudsman Republik Indonesia Perwakilan Sulawesi Selatan dalam Menyelesaikan Laporan Pengaduan Masyarakat di Kota Makassar - Alifianti, Ade; Ansari, Muh Isa; Parawu, Hafiz Elfiansya (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to analyze and describe the performance of the Indonesian Ombudsman Representative for South Sulawesi in resolving complaints reports in Makassar City. This study used qualitative research with descriptive type. The research data were collected through observation, interviews, documentation, and media review. Validation of data was done through source triangulation and technical triangulation and then analyzed through data reduction, data presentation, and data verification. The results showed that the performance of the RI Ombudsman Representative for South Sulawesi in resolving public complaints was quite good. This could  be seen from the clarity of requirements, documents and clarity of procedures and service mechanisms in accordance with the RI Ombudsman Regulation Number 48 of 2020. Although in the aspect of accountability the Ombudsman had not been maximized in transparency. This could be  seen from the report submitted by the Central Ombudsman through the website of the Ombudsman of the Republic of Indonesia which was only a general report.Keywords: Performance, Ombudsman RI, Complaint Report